Avaliação de ferramenta para a escarificação do solo em camadas de forma simultânea - Gassen, José Renê Freitas (2011)
The growing demand for energy that causes the increased traffic of agricultural machinery, larger and more robust, acts negatively on soil compaction, directly and indirectly affecting crop productivity, as many changes in soil physical attributes. As a potential technique to solve this problem has the chiseling, which promotes the disruption of these compacted layers, without causing the inversion of the soil, keeps the plant residues deposited on the surface, improves infiltration, the structure and porosity of the soil and thus facilitates erosion control. However this operation has a high demand for traction. Seeking a more efficient operation of scarification, ie, better utilization of energy, developed and evaluated a tool to break ground in layers simultaneously. For this purpose it was necessary to construct a Structure-Port Mobile Tools capable of performing experimental procedures resulting from the planned treatments. As a mobile source of power was used a Massey Ferguson tractor model MF 275 with 53 kW. The experiment was conducted in the Municipality of Capon Beautiful South, Rio Grande do Sul, in a clayey soil. As a general objective, we sought to answer the following questions: (i) is there any significant difference between chiseling in a single layer or more than one layer, considering the average horizontal force on the drawbar, the specific resistance and the average hourly fuel consumption as criteria for each level of speed? (Ii) how the deepening affects the average horizontal force in the drawbar? And (iii) acts as the advance on the soil area mobilized? Configurations were tested with chiseling of the soil in one, two and three layers, with variations in longitudinal distances between the tips of the spikes. The chiseling treatments in two concurrent 0,15 meters layers and longitudinal distance between the tip ends of 0,30 and 0,40 meters, with one in 0,10 meter of deepening and 0,30 meters advancing presented as the most promising. It was concluded at the end of this work, considering all the tested configurations, there are combinations of deepening, advancing and speed, which proved more efficient than chiseling a single layer.